Environmental change and the timing of the settlement of the Bronze Age Andronovo culture, in far northwest Xinjiang, China. (February 2022) - Dodson, John; Jia, Peter Weiming; Betts, Alison; Cong, Dexin
The relationships between societal and environmental changes have long attracted strong interest amongst scientists. Each of these systems has their own internal dynamics such as the adaptability and social systems built by people; and the feedbacks and controls on environmental systems. North west Xinjiang presents a challenging topographic and climate setting for people. Yet existing evidence shows Bronze Age populations settled into the Bortala Valley as early as the third millennium BCE. The harshness of the region provides a test case for exploring how environmental changes and societal changes may have intertwined. Near the town of Wenquan there is an extensive wetland which contains a sedimentary record covering the last 10, 400 years. The early to mid-Holocene is marked by desert and a lake at Wenquan, but there is little evidence for human activity. By 4500 cal year BP the climate became more humid and soon peak humidity occurred when a regional steppe was developed and small numbers of trees were present on the mountains, also the lake shallowed to become a marsh and peatland. The uplands saw a slight increase in tree cover after this, probably as a result of moisture increase due to some cooling. Later changes in the archaeological record seem to be independent of the timing of any environmental changes, and human impacts on the wetland were small until historical times. In short, the major change from desert to steppe may have enabled people to settle the region, but later changes in the environment were too small to be revealed in the Wenquan sediment data, with the adaptability of societies overcoming any environmental challenges and with land-use practices being too small or localized to impact the palaeoenvironmental record.